The Effect of Nutritioning Interval on Automatic Drip Hydroponic System on Growth and Production of Three Varieties of Lettuce (Lactuca sativa L.) - Suci Ristiyana; Wahyu Indra Duwi Fanata; Tri Wahyu Saputra; Ika Purnamasari; Parawita Dewanti; Rahadian Falqi Taufik (The University of Lampung, 2025)
Lettuce (Lactuca sativa L.) is a leaf vegetable that has a high level of consumer demand and commercial value and can be cultivated using a combination of hydroponic substrate and drip irrigation methods. This research aims to determine the effect of the time interval for providing nutrients on the growth and harvest results of three lettuce plant varieties. Plants were cultivated on cocopeat and husk charcoal media (ratio 1:3) and arranged using a Randomized Block Design (RAK) consisting of two treatments. The first treatment is the nutritional interval which consists of an interval of 2 hours with a discharge of 17 ml (I1), 3 hours with a discharge of 25 ml (I2), and 4 hours using a discharge of 34 ml (I3). The second treatment is the plant variety which consists of the Grand Rapids variety (V1), the Green Coral variety (V2), and the Red Coral variety (V3). The data is analyzed using analysis of variance and if the results obtained are significantly different then a DMRT test will be carried out. The research results showed that the Green Coral lettuce variety was better than the Grand Rapids and Red Coral varieties. This is shown by the results with the highest and best values for the observation variables of number of leaves, plant fresh weight, and chlorophyll content. The nutritional interval which consists of an interval of 2, 4, and 6 hours gave results that were inversely proportional to the variety treatment, that is, they were not significantly different in all observed variables. Keywords: lettuce plants, plant varieties, nutritional interval, substrate hydroponics